Spectroscopic characterization of thiol adducts formed in the reaction of 4-methylcatechol with DPPH in the presence of N-acetylcysteine - Ichitani, Masaki; Okumura, Hisako; Nakashima, Yugo; Kinugasa, Hitoshi; Honda, Mitsunori; Kunimoto, Ko-Ki (European Journal of Chemistry, 2018)
Nucleophiles such as thiol compounds have enhancing effects on the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities of polyphenols. Several authors have suggested that regeneration of the catechol structure from o-quinone plays a key role in enhanced radical scavenging activity. We therefore explored the reaction of 4-methyl catechol (MC) with DPPH in the presence of N-acetylcysteine (NACys) to clarify the mechanism underlying activity enhancement. Four types of NACys adducts were isolated and purified by preparative HPLC after the reactions reached equilibrium and their structures were characterized spectroscopically using UV-Vis absorption, NMR, and LC-MS. Oxidation of MC using a periodate resin and subsequent reaction with NACys were also studied. LC-MS analyses revealed that a mono-NACys adduct is produced as the major product in the reaction of MC quinone with NACys, and direct reduction by NACys occurs in reactions with NACys MC quinones.